2001
DOI: 10.1163/15685380152770363
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in mitochondrial DNA of Near Eastern water frogs with special reference to the systematic status of Cypriote and Anatolian populations (Anura, Ranidae)

Abstract: Water frogs from Anatolia, Syria, Jordan, and central Asia (Turkmenistan, Uzbekistan, Kazakhstan) were compared on the basis of the complete mitochondrial (mt) ND3 gene (340 bp), two anking mt t-RNA gene fragments (26 bp), and a 374 bp fragment of the mt 12S rRNA gene. A total of 27 haplotypes were found among the investigated individuals. Anatolian water frogs differed from Syrian and Jordanian Rana bedriagae by 2.2-3.4% of the analysed sites. The observed divergence (2.8-4.1%) between the Cypriote water frog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Other studies have suggested the existence of cryptic genetic lineages within some amphibian and reptile taxa with apparently continuous geographic distribution in Anatolia (Kyriazi et al, 2008;Plötner et al, 2001;Akın et al, 2010;Fritz et al, 2007). Recent results very similar to the ones here described for Anatololacerta have been recovered for the Eurasian blindsnake, Typhlops vermicularis (Kornilios et al, 2011(Kornilios et al, , 2012 and the Blanus strauchi species complex (Sindaco et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Other studies have suggested the existence of cryptic genetic lineages within some amphibian and reptile taxa with apparently continuous geographic distribution in Anatolia (Kyriazi et al, 2008;Plötner et al, 2001;Akın et al, 2010;Fritz et al, 2007). Recent results very similar to the ones here described for Anatololacerta have been recovered for the Eurasian blindsnake, Typhlops vermicularis (Kornilios et al, 2011(Kornilios et al, , 2012 and the Blanus strauchi species complex (Sindaco et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Ophisops elegans shows four distinct genetic lineages in Anatolia (Kyriazi et al, 2008). The Anatolian water frogs exhibit a similar pattern with various lineages having been identified (Plötner et al, 2001;Akın et al, 2010). Fritz et al (2007) revealed the existence of several mtDNA varieties of Testudo graeca in Anatolia, that were assigned to specific level, and were also confirmed in some cases by a thorough morphological approach (Türkozan et al, 2010).…”
Section: Phylogenetic Resolution Of the Anatololacerta Species Complexmentioning
confidence: 91%
See 2 more Smart Citations
“…However, to incorporate the potential for variation in mutation rate we also calculated divergences using the lower and upper limits of rates reported for anurans in the literature for ND2 (e.g. 0.69% for every million years for Bufo (Macey et al 1998) and 2.4% for every million years for Rana (Plötner et al 2001)). …”
Section: Demographic Expansion Analysesmentioning
confidence: 99%